Pengaruh Penghargaan Ekstrinsik, Penghargaan Intrinsik, Keterlibatan Kerja Terhadap Kesejahteraan Psikologis pada Institut Bisnis IT&B - Tanady, Darwan; Sanjaya, Mega; Novirsari, Emma; Harianto, Adi; Nasib, Nasib (CV. Rayyan Dwi Bharata, 2024)
This study aims to investigate how extrinsic rewards, intrinsic rewards, and levels of work engagement contribute to the psychological well-being of employees in the campus environment of the ITB Business Institute. The research method used is a survey using questionnaires distributed to employees in various departments and units on campus. Extrinsic awards are evaluated through financial recognition and other material awards, while intrinsic awards include recognition of achievement, personal development, and a sense of accomplishment. Job engagement is measured through job satisfaction, commitment to work, and identification with organizational values. The collected data was analyzed using regression techniques to identify the relationship between independent variables (extrinsic rewards, intrinsic rewards, and work engagement) and dependent variables (psychological well-being). The findings of this study are expected to provide in-depth insights into the factors that affect the psychological well-being of employees on the campus of the ITB Business Institute. The results of this study are expected to provide recommendations to campus management in improving reward strategies and work engagement management to support the psychological well-being of employees. The practical implications of this research are expected to help create a more satisfying and productive work environment for all campus members.